Very-late-onset pyridoxine-dependent seizures not linking to the known 5q31 locus - Kabakus, Nimet; Aydin, Mustafa; Ugur, Sibel A.; Durukan, Mehtap; Tolun, Aslihan (Wiley-Blackwell, 2008)
[Abstract Not Available]
Keywords: child; genetic; late-onset pyridoxine dependency; seizure